2007
DOI: 10.5713/ajas.2007.1243
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probiotic Lactobacillus reuteri Pg4 Strain on Intestinal Characteristics and Performance in Broilers

Abstract: This study was conducted to evaluate the feasibility of using L. reuteri Pg4, a strain isolated from the gastrointestinal (GI) tract of healthy broilers, as a probiotic. In preliminary in vitro studies the Pg4 strain was proven capable of tolerating acid and bile salts, inhibiting pathogenic bacteria and can adhere to intestinal epithelial cells. The probiotic properties were then evaluated on the basis of the broiler's growth performance, intestinal microbial population and cecal volatile fatty acid and lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
8
27
2
2
Order By: Relevance
“…Kalavathy et al (2003) reported that the supplementation of probiotics in broiler diets improved their body weight gain and feed conversion ratio from 1 to 42 days of age. Yu et al (2007) also showed that the supplementation of an intestinal Lactobacillus reuteri strain to a wheatbased diet increased body weight gain of broilers from 1 to 21 days of age. Moreover, Khaksefidi & Ghoorchi (2006) reported that the body weight gain and feed conversion ratio of broilers fed probiotics …”
Section: Effect Of Probiotics On Growth Performancementioning
confidence: 90%
See 1 more Smart Citation
“…Kalavathy et al (2003) reported that the supplementation of probiotics in broiler diets improved their body weight gain and feed conversion ratio from 1 to 42 days of age. Yu et al (2007) also showed that the supplementation of an intestinal Lactobacillus reuteri strain to a wheatbased diet increased body weight gain of broilers from 1 to 21 days of age. Moreover, Khaksefidi & Ghoorchi (2006) reported that the body weight gain and feed conversion ratio of broilers fed probiotics …”
Section: Effect Of Probiotics On Growth Performancementioning
confidence: 90%
“…These results are in accordance with those of Kizerwetter-Swida & Binek (2009) who indicated that the Lactobacillus salivarius decreased the number of Clostridium perfringens and Salmonella Enteritidis in the group of chickens treated with Lactobacillus. Yu et al (2007) evaluated the effects of probiotic Lactobacillus reuteri strain Pg4 on the performance and intestinal characteristics of broilers, and reported that the Lactobacillus populations in the ileum, crop, and cecum of the broilers fed probiotics were higher than those in the control group. Other studies have also shown the potential of probiotics to populate the gut microflora of broiler chickens with beneficial bacteria and to supress the growth potentially pathogenic bacteria (Vicente et al, 2008).…”
Section: Effect Of Probiotics On Gut Microbial Populationmentioning
confidence: 99%
“…Lactobacillus culture into broiler feed result in an increase in feed conversion ratio (Yu et al, 2007;Chen et al, 2016). It is noteworthy that the different effects of probiotics, including relation of intestinal microflora (Yu et al, 2007;Chen et al, 2016) and immune system ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the different effects of probiotics, including relation of intestinal microflora (Yu et al, 2007;Chen et al, 2016) and immune system ). In the current experiment, the results showed that the kefir makes suitable environment for microbial and it would be helped on the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in their study Lactobacillus acidphilus shows 39.2% adhesion to xylene. As suggested by others, the high cell surface hydrophobicity of the present strain could indicate its potential to attach to the epithelial cell lining of the intestine and resist the movement of digesta [32]. Ram and Chander [30] have studied the influence of different growth media and observed that maximum percent (80-89%) adhesion of B. bifidum was with Motility Indole Lysine Sulfide medium (MILS medium) followed by MRS-lactose broth (68-79%).…”
Section: Cell Surface Hydrophobicitymentioning
confidence: 99%